Identification of serum proteins in dogs naturally infected with Anaplasma phagocytophilum and Borrelia burgdorferi: a pilot study - KOCATURK, M; MARTINEZ, LF; ESCRIBANO, D; SCHANILEC, P; LEVENT, P; SARIL, A; MARTINEZ-SUBIELA, S; TVARIJONAVICIUTE, A; CIHAN, H; YALCIN, E; CERON, JJ; YILMAZ, Z (Journal of the Hellenic Veterinary Medical Society, 2022)
Serum proteomic analysis would aid in better understanding the pathophysiology of several diseases. The aim of this study was to identify the serum proteomes of dogs with anaplasmosis and Lyme disease using a proteomic approach. Diseases were diagnosed by a commercial rapid in-clinic ELISA. Borrelia antibodies were evaluated by IFAT. Four groups were designated: symptomatic dogs with anaplasmosis (n=5), dogs with Lyme disease (n=5), dual-positive dogs (n=5), and healthy control dogs (n=5). Serum samples were collected before treatment. Two-dimensional electrophoresis of pooled samples in each group were run in triplicate. Ten out of 57 differentially expressed spots between groups were evaluated for identification by mass spectrometry. Compared to those of controls, levels of vitamin D-binding protein (VDBP), glycoprotein-9 (GP9) and kininogen-1 (KGN-1) decreased, while haptoglobin (Hp) and immunoglobulin (Ig) heavy chain levels increased in dual infection group. Serum apolipoprotein-A1 (Apo-A1) levels decreased in dogs with anaplasmosis, Lyme disease and dual infections compared to those in control dogs. Serum clusterin levels decreased in dogs with anaplasmosis but were not differentially expressed in dogs with Lyme disease or dogs with dual infections compared to those in control dogs. Calpain-3 decreased in dogs with anaplasmosis and Lyme disease. This study showed that many protein levels might be changed in dogs with naturally acquired anaplasmosis and Lyme disease. Understanding the role of these proteins in different biological processes can provide information of interest for diagnostic and therapeutic approaches for these clinical conditions.